The association between dietary diversity, social assistance, and coping strategy with household food security during COVID-19 in Tulungagung District, East Java - Novianti Tysmala Dewi Novi; Dwi Nastiti Iswarawanti; Novia Silvia Hardiany (Indonesian Nutrition Association, 2022)
Background : Food insecurity is still prevalent in Indonesia and COVID-19 impacts led to severe and widespread increases in food insecurity, affecting vulnerable households with impacts expected to continue into 2022 and possibly beyond. Objective : This study aimed to determine the association between dietary diversity, social assistance, and coping strategies with food security during COVID-19 in Tulungagung, East Java. Methods : This cross-sectional study was conducted in Tulungagung District, East Java with interviewed using telephone from May to July 2021. Multistage random sampling was conducted to 187 parents (mother or father). The study used structured questionnaire for socio demographic background, Household Food Insecure Assess Scale (HFIAS), dietary diversity scale, coping strategy index instruments to collect the data. Results : This study found the prevalence of food insecurity in Tulungagung were 56.1%. There was association between income (p=0.021, OR= 2.388(1.123-5.079)), dietary diversity (p=0.007, OR=3.400(1.440-8.200)), number of coping strategies (p=<0.001, OR=10.020(5.055-9.861)), and coping strategies food compromisation (p=<0.00, OR=13.337(5.835-3.485)) with food security. Conclusions : Most households have faced food insecurity because of lower income during the pandemic, have low dietary diversity, and tend to use coping strategy to survive. By this finding, it is important for government to give priority and focus on vulnerable household in social assistance for the long term and more focused to build up human capital among households through skill and training to ensure the resilience of food security.